2019
DOI: 10.1177/1526602819857601
|View full text |Cite
|
Sign up to set email alerts
|

Complex Endovascular Aortic Repair With a Branched Endograft to Revascularize 5 Renovisceral Vessels and an Intercostal Artery in a Marfan Patient

Abstract: Purpose: To report a case of thoracoabdominal aortic aneurysm (TAAA) repair treated with a multibranched stent-graft including a prophylactic branch for a large intercostal artery in a Marfan patient at risk for spinal cord ischemia (SCI). Case Report: A 43-year-old man with Marfan syndrome presented with a type IV thoracoabdominal aortic aneurysm (TAAA) and history of multiple previous cardiac and aortic operations over the past 28 years. The maximum diameter of the aneurysm was 60 mm. The patient had 2 right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Moreover, the favorable angulation and diameters of the 7 TVs allowed them to be included in the branched device to decrease the risk of renal impairment and/or visceral malperfusion. Since the use of such a large number of branches was supported by recent experiences suggesting the feasibility of F/B-EVAR for 5 and 6 target vessels, 12,13 a 7-branch stent-graft was included in the options discussed with the patient, who agreed to this more complex treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the favorable angulation and diameters of the 7 TVs allowed them to be included in the branched device to decrease the risk of renal impairment and/or visceral malperfusion. Since the use of such a large number of branches was supported by recent experiences suggesting the feasibility of F/B-EVAR for 5 and 6 target vessels, 12,13 a 7-branch stent-graft was included in the options discussed with the patient, who agreed to this more complex treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 15 Intercostal preservation has also been demonstrated during index fenestrated-branched endovascular aortic repair with dedicated side stents or scallops. 16 , 17 Intercostal artery stenting is rarely utilized in intercostal artery preservation during treatment of intercostal patch aneurysms but is feasible, particularly when parallel grafting can be utilized as demonstrated in a similar case by Tjaden et al. 18 That case also demonstrates the importance of test balloon occlusion of the intercostals with continuous neurologic monitoring prior to finalizing the operative plan, as was done with our patient as well, to mitigate spinal cord ischemia risk.…”
Section: Discussionmentioning
confidence: 56%
“…The intercostal artery was revascularized to decrease the risk of spinal cord ischemia. 8 Several investigators have reported the feasibility and safety of F/B-EVAR. [1][2][3][21][22][23] The 30-day mortality was 1/12 patient, which is accepted as regard to the rate reported in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 2 case reports addressed the feasibility of F/B-EVAR for 5 and 6 target visceral vessels (TVs) in the treatment of TAAA with renovisceral arterial anatomical variations demonstrating technical feasibility of F/B-EVAR even when the number of TVs exceeds 4. 7,8 However, whether time and effort to connect additional TVs is justified or may complicate outcomes of an already complex endovascular procedure is unclear, as well as patency rates of small renovisceral vessels.…”
Section: Introductionmentioning
confidence: 99%